EQUITY COSTS AND FINANCIAL PERFORMANCE OF LICENSED DEPOSIT TAKING CREDIT CO-OPERATIVE SOCIETIES IN KENYA - Kenneth Mwangi Muriuki; Agnes Njeru; Anthony Gitonga Kirimi (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
International and local researchers have extensively studied the impact of equity financing on business financial performance, as the cost of equity represents the required return investors expect for assuming ownership risk (Kenton, 2025). This metric is vital for capital budgeting and investment decisions. Compliance with equity regulations can be complex and costly, sometimes involving borrowing, non-declaration of dividends, and other financial sacrifices that may affect shareholders and employees negatively. In Kenya, Savings and Credit Cooperative Societies (SACCOs) play a significant role, directly or indirectly impacting around 10 million Kenyans and holding over 80% of the country’s saving. The Sacco Society Regulatory Authority (SASRA) licenses and regulates deposit-taking SACCOs, imposing strict equity adequacy requirements. Out of 245 SACCOs applying for licenses by 2019, only 177 were approved; by 2022, after suspensions and new approvals, 176 remained licensed. Many SACCOs struggle to meet these equity thresholds. Balancing compliance costs without compromising financial performance or shareholder wealth maximization is critical. This study investigated the relationship between equity cost compliance and financial performance of licensed deposit-taking SACCOs in Kenya. Using secondary data from audited financial statements, the study employed logistic multiple regression analysis focusing on Shareholders’ Equity, Total Liabilities, and Dividends Paid. Results indicated that effective management of equity financing, minimizing equity costs, is essential for the financial stability and improved performance of SACCOs.